Herbal Soap Production Training Based on Fresh Fruits to Enhance Teachers’ Skills at MI Assalafiyah, Kediri Regency - Astuti, Engrid Juni; Hidayati, Ika Ratna; Syifa’, Nailis; Wardoyo, Sri Sunaringsih Ika (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance teachers’ skills and creativity in producing natural herbal soaps derived from fresh fruits. The program was implemented at MI Assalafiyah, Kediri Regency, using socialization and hands-on training methods. The training began with the administration of a pre-test, followed by the delivery of instructional materials and practical sessions. A post-test was conducted at the final stage to evaluate participants’ understanding and the skills acquired. The results indicate that the herbal soap–making training was highly beneficial in equipping teachers with new practical skills. A significant improvement in participants’ competencies was observed, as reflected in the increase in mean scores from the pre-test (50.38 ± 19.36) to the post-test (85.33 ± 11.06). Furthermore, this training has the potential to be integrated as an extracurricular activity in schools to support students’ skill development, particularly in herbal soap production.